2019
DOI: 10.3390/app9194183
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Nanocatalysts on Hydroxyapatite: Green Oxidation of Alcohols and Reduction of Nitroarenes in Water

Abstract: A green procedure is described for supporting Pd nanoparticles on hydroxyapatite (HAP), which serves as a highly-stable heterogeneous catalyst displaying excellent activity for the aqueous expeditious reduction of nitroaromatics to the corresponding amines with sodium borohydride, and oxidation of primary and secondary alcohols by hydrogen peroxide with high yields and selectivities. The structural features of the prepared catalyst are confirmed by latest techniques including field emission scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…In the last decade, numerous studies have reported the preparation of various types of nanostructures to be superior in applications with different purposes such as biomedicine and catalysis. [26][27][28][29][30][31][32][33][34][35][36] Fluorescent carbon quantum dots (CQDs) are a fascinating class of nanostructures compared to metallic nanoparticles in various purposes due to their low toxicity, biodegradability and biocompatibility. 1,[37][38][39][40] Therefore, they are considered as superior alternatives for metal-based nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, numerous studies have reported the preparation of various types of nanostructures to be superior in applications with different purposes such as biomedicine and catalysis. [26][27][28][29][30][31][32][33][34][35][36] Fluorescent carbon quantum dots (CQDs) are a fascinating class of nanostructures compared to metallic nanoparticles in various purposes due to their low toxicity, biodegradability and biocompatibility. 1,[37][38][39][40] Therefore, they are considered as superior alternatives for metal-based nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…To verify the catalytic activity and chemoselectivity of the v-SiO 2 NRs@Pd nanostructured catalyst, we conducted the hydrogenation of various substituted nitroaromatics at room temperature; a reaction that has important impact in many industries, including environmental safety. [47][48][49][50] Our designed nanostructured catalyst presented superb catalytic activity for the selective hydrogenation of nitroaromatics in aqueous solution (Table 1). The procedure was accomplished under eco-friendly mild conditions, attaining high yields for the hydrogenation of substituted nitroaromatics to the corresponding aminoaromatics.…”
Section: Resultsmentioning
confidence: 99%
“…In the last years, various biomaterials such as calcium hydroxyapatite Ca 10 (PO 4 ) 6 (OH) 2 (CaHAP) have been used for bioactive coating of MNPs in order to increase their biocompatibility, chemical stability, and high thermal stability. HAp has the mesoporous solid support with the unique advantages such as catalyst support, weak acid–base properties, high adsorption capacity, and ion exchangeability 7,13–19 . On the other hand, it has been evidenced that the immobilization of homogeneous Schiff base metal complexes onto/in solid supports is one of the most efficient procedures for preparation of heterogeneous metal‐imine complexes 20 .…”
Section: Introductionmentioning
confidence: 99%